NOVEL APPROACH TO ANTITHROMBOTIC TREATMENT OF ACUTE CORONARY PATIENTS WITH RIVAROXABAN - I. N. Bokarev; A. V. Golub (Российский кардиологический журнал, 2015)
Antithrombotic treatment of acute coronary syndrome leads to much better outcomes of the disease. The article focuses on the arguments and evidence for the addition to antiplatelet drugs the rivaroxaban 2,5 mg two times per day for secondary prevention of AMI.